Anonymity Phenomenon In Base Fwb (Friends With Benefits) On Twitter And Motivation For Freedom Of Sexual Expression - Intan Ayu Dewintya Kirana (Budapest International Research and Critics University, 2022)
Anonymity has ( become a thing that is often found on social media today. Anonymity refers to an environment that involves secrets, hidden identities, and masks of personality. Anonymity is characterized by the